A new subspecies of Batagur affinis (Cantor, 1847), one of the worlds most critically endangered chelonians (Testudines: Geoemydidae) - Praschag, Peter; Holloway, Rohan; Georges, Arthur; Päckert, Martin; Hundsdörfer, Anna K.; Fritz, Uwe (Zootaxa, 2009)
Estuarine Batagur are among the most critically endangered chelonian species. We assess the taxonomic status of the recently discovered Cambodian relic population of Batagur by phylogenetic analyses of three mitochondrial (2096 bp) and three nuclear DNA fragments (1909 bp) using sequences from all other Batagur species and selected allied geoemydids. Furthermore, we calculated haplotype networks of the mitochondrial cytochrome b gene for Cambodian terrapins, B. affinis, B. baska, and B. kachuga and compare external morphology of estuarine Batagur populations. Genetically, Cambodian Batagur are closely related with, but distinct from B. affinis from Sumatra and the west coast of the Malay Peninsula. Morphologically, Cambodian Batagur resemble the distinctive B. affinis populations from the eastern Malay Peninsula that were not available for genetic study. We suggest that the Batagur populations from the eastern Malay Peninsula and Cambodia represent a new subspecies of B. affinis that once was distributed in estuaries surrounding the Gulf of Thailand (Batagur affinis edwardmolli subsp. nov.). Its patchy extant distribution is most probably the result of large-scale habitat alteration and century-long overexploitation. In addition, our phylogenetic analyses suggest repeated switches between riverine and estuarine habitats during the evolution of the extant Batagur species.